Engagement sensitive visual stimulation - Deepesh Kumar; Anirban Dutta; Abhijit Das; Uttama Lahiri (PAGEPress Publications, 2016)
Stroke is one of leading cause of death and disability worldwide. Early detection during golden hour and treatment of individual neurological dysfunction in stroke using easy-to-access biomarkers based on a simple-to-use, cost-effective, clinically-valid screening tool can bring a paradigm shift in healthcare, both urban and rural. In our research we have designed a quantitative automatic home-based oculomotor assessment tool that can play an important complementary role in prognosis of neurological disorders like stroke for the neurologist. Once the patient has been screened for stroke, the next step is to design proper rehabilitation platform to alleviate the disability. In addition to the screening platform, in our research, we work in designing virtual reality based rehabilitation exercise platform that has the potential to deliver visual stimulation and in turn contribute to improving one's performance.